Analysis of Liquidity, Profitability, Risk and Financial Distress: A Case Study of Dr. Reddy’s Laboratories Ltd. - Viswanatha Reddy, C. (Indian Journal of Finance, 2012)
Liquidity is the ability of an organization to meet its financial obligations during the short-term and to maintain long-term debt-paying ability. The long-term survival depends on the satisfactory income earned by it. A sound liquidity leads to better profitability, and in turn reduces the probability of default risk in the future. Further, the risk and return are very important aspects to be considered while making any decisions regarding a company's finances. Predicting enterprise failures constitutes one of the most important activities in supervising enterprise risks and/or variables. The term enterprise failure is a definable phenomenon: which encompasses, for instance, failure to cover external debts, exceeding budget limits, failure to effect payment to suppliers, incurring losses, etc. Therefore, a study of liquidity, profitability, and their association with risk, assessing the financial position (financial distress/bankruptcy) is very much necessary to evaluate the financial strength of a company. Financial distress is a tight cash situation in which a business cannot pay the owed amounts on the due date. When a firm is under financial distress, the situation sharply reduces its market value, and larger customers may cancel their orders. A firm in financial distress may face bankruptcy or liquidation leading to delay in meeting its liabilities. This paper attempts to study the association between liquidity, profitability and risk factor. The Altman's Z-score model has been employed by the researcher to predict the risk of financial distress of Dr. Reddy's Laboratories Limited, from the year 2005-2011. The results indicate that the liquidity and solvency position of the company have been satisfactory. The Z-score analysis revealed that the company was not suffering from financial distress and there are indications of turnaround activities already undertaken by the company.